The Influence of Viral Marketing on Tiktok Shop Live Streaming on Erigo Product Purchase Decisions - Faizal Kamay; Prihatin Dwihantoro (Publikasi Indonesia, 2024)
Viral marketing has become a popular phenomenon in efforts to disseminate information and marketing of a product or service. Information and content is disseminated on digital media in social networks. This study used a quantitative method by distributing questionnaires with the Google Form platform which was shown to student respondents in Communication Studies, University of Muhammadiyah Magelang. Respondents were active students in semesters 2, 4, 6, and 8 of the Communication Studies study program and there were 92 respondents. The data that has been collected is then analyzed using statistical techniques, including validity tests, reliability tests, normality tests, and regression analysis tests to see the magnitude of the influence between the variables. The purpose of this research is to find out the effect of live streaming on the tiktok shop on purchasing decisions for Erigo products, to analyze the effect of live streaming on tiktok shops to viral marketing, to analyze the influence of viral marketing on purchasing decisions for Erigo products. The results of this study can provide valuable insights for marketing practitioners in designing more effective viral marketing strategies. The results of this study indicate that viral marketing on live streaming of the Tiktok brand Erigo has a positive and significant influence on purchasing decisions for the Erigo brand.